Oye Como Va! : Hybridity and Identity in Latino Popular Music - Pacini Hernandez, Deborah (Book collections on Project MUSE., 2010)
"In Oye Como Va!, Deborah Pacini Hernandez traces the trajectories of various U.S. Latino musical forms in a globalizing world, examining how the blending of Latin music reflects Latino/a American lives connecting across nations. Exploring the simultaneously powerful, vexing, and stimulating relationship between hybridity, music, and identity, Oye Como Va! asserts that this potent combination is a signature of the U.S. Latino/a experience."--From publisher's description.